Building the Path to Success - Repas, Ana; Marič, Miha (Izzivi managementa talentov, 2025)
In the modern world, where people set a variety of goals and strive to achieve them, there is multitude different interpretations of success. Just as there is a diverse range of definitions of success, there are many different feelings that individuals experience upon attaining it. The ultimate success is the result of a long and demanding journey, where self-discipline, motivation, self-confidence, talent, learning ability, communication, and perseverance of the individual are put to the test. Failures, which are an inevitable part of this journey, bring valuable lessons through which we learn the most about ourselves, our abilities and limits. Each individual carries their own path, which can be filled with challenges or simplicity. This contribution focuses on the concept of success and segments on the path to its achievement.